Communication strategy of palm oil farmers In increasing oil palm productivity In the Bual-Bual Village, district of East Kutai - Aldryansyah; Angga Intueri Mahendra Purbakusuma (Jurnal Mantik, 2022)
This study aims to determine the communication strategies carried out by oil palm farmers in an effort to increase oil palm productivity, as well as inhibiting and supporting factors for oil palm productivity in Bual-Bual Village, East Kutai Regency. The method used in this research is a qualitative research method with a descriptive approach. The analytical method used in this study is the data analysis model of Miles and Huberman. Sample determination using purposive random sampling method to oil palm farmers in Bual-Bual Village. The oil palm farmers in Bual-Bual Village are independent farmers and plasma farmers who enter into the partnership. Limited land ownership, which means less attention is paid to the intensification of fertilizer application, fluctuations in oil prices, and a decrease in the purchasing power of oil palm owned by independent smallholders are some of the factors that hinder thes productivity of oil palm independent smallholders. In contrast, plasma farmers experience less optimal maintenance as a result of challenging road access. Innovation strategies, quality strategies, and cost-cutting strategies are the implemented communication strategies